2022
DOI: 10.3390/microbiolres13040069
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus M247: Characteristics of a Precision Probiotic Instrument for Gynecological and Urinary Well-Being

Abstract: The altered patterns of a microbial population colonizing an organ are increasingly recognized as a relevant item in human disease pathogenesis. The female urogenital tract is no exception, as some vaginal microbiota patterns, named community state types (CSTs), and urinary tract microbiota patterns, named urotypes (UTs), have been linked to viral, inflammatory, and gestational diseases. Treating these conditions is an issue, as antibiotic therapies alone are not always effective. Lactobacillus crispatus M247 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A more recent comparative genomic study identified prophage sequences in 90 out of 105 L. crispatus strains isolated from various sources, with complete prophage more likely in human strains [10]. In this work, we determined the complete genome sequence of L. crispatus strain M247, a newborn faecal isolate largely studied for its probiotic activity and characterized by a strong aggregation phenotype and adherence to intestinal mucus [14][15][16][17][18][19]. It has been reported that M247 has beneficial effects on intestinal inflammatory disorders [20][21][22], helps to counteract vaginal dysbiosis [23] and probably contributes to papilloma virus clearance [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent comparative genomic study identified prophage sequences in 90 out of 105 L. crispatus strains isolated from various sources, with complete prophage more likely in human strains [10]. In this work, we determined the complete genome sequence of L. crispatus strain M247, a newborn faecal isolate largely studied for its probiotic activity and characterized by a strong aggregation phenotype and adherence to intestinal mucus [14][15][16][17][18][19]. It has been reported that M247 has beneficial effects on intestinal inflammatory disorders [20][21][22], helps to counteract vaginal dysbiosis [23] and probably contributes to papilloma virus clearance [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we determined the complete genome sequence of L. crispatus strain M247, a newborn faecal isolate largely studied for its probiotic activity and characterized by a strong aggregation phenotype and adherence to intestinal mucus [14–19]. It has been reported that M247 has beneficial effects on intestinal inflammatory disorders [20–22], helps to counteract vaginal dysbiosis [23] and probably contributes to papilloma virus clearance [24].…”
Section: Introductionmentioning
confidence: 99%
“…In January 2020, our department started to use the well-documented M247 strain of L. crispatus in women undergoing IVF [32]. This study is therefore concerned with the retrospective analysis of the results gathered from January 2020 to December 2021.…”
Section: Introductionmentioning
confidence: 99%